ANALISIS KEMAMPUAN MEMBERIKAN ALASAN DAN MENGINTERPRETASI SUATU PERNYATAAN - Istiqomah Yustiningsih; Ila Rosilawati; Nina Kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
This research aimed to describe the ability of students to give reason and interpreting a statement on the acid-base matery through the application of guided inquiry for students groups of high, intermediate and low level group.  The subjects were students of class XI IPA2 SMA Negeri 1 Bandar Sribhawono. This research used the pre-experimental method  with a one-shot case study design.  It was a descriptive research.  Based on the result of data analysis summarized that ability of give reasons in high level group: mainly were very good and the others were good .  In  intermediate level group, almost half were enough, mainly were good and the others were very good.  In low level group, almost half were enough, mainly were good and the others were very good.  The ability of interpreting a statement in high level group: mainly were very good and the others were good. In  intermediate level group, just small part were excellent, almost half were good, and the others were enough.  In low level group, just small part were excellent, almost half were good and the others were enough.  Therefore, guided inquiry learning can be developing students' ability to give reasons and interpreting a statement.Kata kunci:  pembelajaran inkuiri terbimbing, kemampuan memberikan alasan, menginterpretasi suatu pernyataan, kelompok kognitif.